IMPLEMENTATION OF TECHNIQUE METHOD FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) FOR SMARTPHONE SELECTION - Mohamad Arifin; Listiarini Edy Sudiati; Ninik Haryani (SOSCIED, 2022)
The rapid development of technology has impacting on people's lives, including in the telecommunications sector. Various smartphone brands began to emerge by offering various advantages and characteristics of each. In some countries, smartphones have become a lifestyle and even a indicator of one's economic level. It's reasonable, considering that smartphones are never separated away from a person's activities, wherever and whenever there are. Many alternatives option makes some people confused in making choices when they are going to purchase a smartphone, so the manufacture of a smartphone selection support system is developed. TOPSIS method is a simple method that is able to provide alternative option based on the highest value of input preferences. The preferences used are taken from popular criteria when buying a smartphone such as; price, RAM, memory, camera, and battery capacity.